General, Applied and Systems Toxicology 2009
DOI: 10.1002/9780470744307.gat043
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives toIn vivoStudies in Toxicology

Abstract: Toxicology or its appplied product evaluation function (also called safety assessment) has now been in the forefront of the public's interest and expectations since at least the Second World War. As our understanding increased, a range of test designs and experimental methods using intact higher animals rapidly developed and came to be accepted in regulation and law. However, as we have come to understand more of both how biological systems work and of the molecular and cellular mechanisms that under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 127 publications
0
7
0
Order By: Relevance
“…Substances are classified in more or less toxic potential according to the IC 50 value: i) IC 50 <10 µg/mL is a very toxic substance, ii) IC 50 = 10-100 µg/mL is a toxic substance, iii) IC 50 = 100-1000 µg /mL is a harmful substance, and iv) IC 50 > 1000 µg/mL is a non-toxic substance (Gad-Shayne, 2009). According to this classification, oregano and mint oils might be considered potentially toxic to human cells (NGM) and potentially very toxic to murine cells (NIH-3T3) in the conditions tested.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…Substances are classified in more or less toxic potential according to the IC 50 value: i) IC 50 <10 µg/mL is a very toxic substance, ii) IC 50 = 10-100 µg/mL is a toxic substance, iii) IC 50 = 100-1000 µg /mL is a harmful substance, and iv) IC 50 > 1000 µg/mL is a non-toxic substance (Gad-Shayne, 2009). According to this classification, oregano and mint oils might be considered potentially toxic to human cells (NGM) and potentially very toxic to murine cells (NIH-3T3) in the conditions tested.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…(Gad, 2009) reported that IC 50 value lower than 10 μg/mL is very toxic, while 10–100 μg/mL is toxic. In this study, the cells were still able to survive without any sign of toxicity for dilaurylazelate ester; thus, it was proven to be non-toxic in this MTT assay compared with AzA and is safe to be used in pharmaceutical applications [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that ethylene oxide is an important compound of sucupira oil and is mainly responsible for this effect with a cellular influx of 47.0 µg/mL (Dutra et al, 2012). A reference half maximal inhibitory concentration <10 mg/mL is considered highly toxic according to published guidelines, and it is therefore possible to deduce that this active compound indeed has high toxicity (Santos Pimenta et al, 2003;Dutra et al, 2008;Gad, 2009).…”
Section: Discussionmentioning
confidence: 99%